Adolescents disposition towards stress and perception that their failure depends upon their peers - PAWANDEEP KAUR (Journal of Advanced Research in Social Sciences and Humanities, 2020)
Aim: This paper seeks to understand whether or not adolescents’ success and failure are determined by their peers and whether or not adolescents are pressured by their friends.Method: Chandigarh, India, public and private institution cross-sectional study. Chandigarh’s eighth, ninth, and tenth graders provided the samples. One thousand students from each of the city of Chandigarh’s 20 public and 20 private schools provided a total of 50 samples. Microsoft Office Excel 2007 was used for the data entry. Frequency tables, charts, and cross tables were used in the analysis. The chi-square test and the correlation coefficient were used to determine the degree of significance between the variables.Findings: Adolescents can’t imagine life without their peers, who play a pivotal role in shaping their identities and behaviors. Close friends share a special bond based on their interests, passions, and worries. Adolescents will resort to strategies to gain their peers’ respect and acceptance. They are constantly influenced by their peers and adopt their attitudes, behaviors, and practices. Involvement in social circles is crucial, but it comes with a heavy price: one’s social standing among their contemporaries can determine success or failure. They are constantly pressured to conform to the norms of their peers and are often teased or picked on if they don’t. Adolescents are especially vulnerable to the effects of peer pressure because their success or failure often depends on their peers.Implications/Novel Contribution: Adolescents will be able to use the findings to better understand the impact of peer pressure on decision-making. Thanks to the findings, parents will be better equipped to help their children overcome behavioral and social difficulties. They also give their kids the space and direction they need to become independent, responsible adults.